DETERMINASI PENGUNGKAPAN EMISI KARBON: PERAN PROFITABILITY, ENVIRONMENTAL PERFORMANCE, DAN GENDER DIVERSITY: DETERMINANTS OF CARBON EMISSION DISCLOSURE: THE ROLE OF PROFITABILITY, ENVIRONMENTAL PERFORMANCE, AND GENDER DIVERSITY IN ENERGY SECTOR COMPANIES - Wiguna, Meilda; Hardi; Hariyani, Eka; Afifah, Ulfa (Universitas Riau, 2025)
Since carbon emissions are becoming a worldwide problem, businesses are being urged to increase environmental reporting's openness. As seen by coal production surpassing the national target in 2023 at 703.14 million tons, Indonesia's energy industry continues to be the biggest source of carbon emissions. Nonetheless, energy corporations continue to disclose carbon emissions at a comparatively low level. This study aims to investigate how energy companies listed on the Indonesia Stock Exchange (IDX) disclose carbon emissions in relation to gender diversity, environmental performance, and profitability. The impact of independent variables on disclosure of carbon emissions is investigated using multiple linear regression analysis. The research findings indicate that profitability, environmental performance, and gender diversity have a positive and significant effect on carbon emission disclosure. It is anticipated that the results would shed light on the variables influencing environmental transparency and help formulate policy suggestions to improve disclosure procedures and sustainability in Indonesia's energy industry. Theoretically, these findings reinforce the relevance of Legitimacy Theory in explaining the drive of energy companies to increase carbon emission disclosures in order to maintain social acceptance and address public pressure